PENGEMBANGAN MODEL PEMBELAJARAN PASSING PERMAINAN SEPAK BOLA DI SMP NEGERI 7 WASILEI HALMAHERA TIMUR - Hamid Ngolo; Mukhlis Nur Abdul (IKIP Budi Utomo Malang, 2018)
The purpose of the study was to develop a model of passing learning in football games for eighth grade students of Wasilei 7 Middle School, East Halmahera Regency. Based on the results of interviews with the physical education teacher on March 8, 2018 the teacher said that when students received their material they were not serious, what was explained by the physical education teacher was not noticed by the students and they always played. The physical education teacher agrees if I make / develop a passing learning model in class VIII of SMP Negeri 7 Wasilei. East Halmahera Regency. The study was conducted at SMP Negeri 7 Wasilei. East Halmahera Regency. The review of the experts consists of 2 experts namely expert football coaches, expert physical education teachers. and the trial subjects consisted of: (1) small group trials using 8 students, and (2) large group trials or field trials consisting of 10 students (the rest of the small group trials). The results of the research based on the expert evaluation of the soccer coach found that the average percentage was 85.68%, and the expert evaluation of the teacher training was known as an average percentage of 90.25% so that this model could be used. The overall results of the 100% large group trial data. And 100% small group trials. So that the model of passing learning in soccer games at Wasilei 7 Public Middle School, East Halmahera District can be used